Combining PCR to detect junction fragments and deleted exons in the prenatal diagnosis of BMD can effectively identify maternal cell contamination - Cai, Lidan; Li, Wei; Zhong, Min (Frontiers in Medicine, 2025)
BackgroundThe junction fragment after the DMD gene deletion has been identified as a new specific DNA sequence formed by the reconnection of the ends. Our study aims to report a novel method for prenatal diagnosis of BMD by using PCR to detect junction fragments and deleted exons.MethodsWe performed the prenatal diagnosis of a fetus with deletional BMD in this study. The proband of this family was the deletion of exons 3 to 5 of the DMD gene. The junction fragment primer designed after locating the breakpoint was used to PCR-amplify the junction fragments of the villus sample and the amniotic fluid genomic DNA. The exon 3 primer was used to amplify the deletion exons of the DMD gene from the villus sample and the amniotic fluid genomic DNA, respectively. At the same time, sex identification was carried out. Finally, the diagnosis results were analyzed.ResultsThe diagnosis of villus sampling was a contradictory result of obtaining the DMD gene deletion junction fragment and the absence of the exon deletion in the male fetus, suggesting that the villus sample was contaminated by maternal cells and the test was unsuccessful. The subsequent diagnosis of amniotic fluid was that the male fetus detected both the junction fragment and the corresponding exon deletion, and was diagnosed as a male fetus with BMD.ConclusionsCombining PCR to detect junction fragments and deleted exons in the prenatal diagnosis of BMD can effectively identify maternal cell contamination. The results were confirmed to be highly accurate and specific.